The Dilemma of Multi-Role Balinese Working Women in Achieving Self-Harmony - Ida Bagus Gde Agung Yoga Pramana; Ida Ayu Ambarini Saraswati; I Putu Dharmawan Pradhana (Psikostudia : Jurnal Psikologi, 2025)
Bali is known for its strong traditions and culture where women play an important role in defending these values. In the midst of modernization, Generation Z women in Bali, especially in Denpasar City and Badung Regency, face challenges in balancing their roles as workers, wives, mothers, and members of indigenous peoples. This study aims to understand how Balinese women workers who marry at a young age achieve harmony in themselves in the midst of the complexity of multi-role undertaken. This research uses a qualitative method with a phenomenological approach. The research sample consisted of four Balinese women generation Z who were married and worked in the government, private, or entrepreneurial sectors in Badung Regency and Denpasar City. Data were collected through in-depth interviews, passive participation observations, and documentation, which were then analyzed using the Miles and Huberman models with the help of NVivo 14 software. The results of the study show that Balinese female workers experience role conflicts, time conflicts, and behavioral conflicts, which have an impact on work-family conflict and work stress. The main factors that affect this imbalance include triple roles, quarter life crisis, marriage culture shock, and job hopping. To overcome these challenges, the informants apply coping strategies such as work-life balance strategies, role management, time management, outsourcing, and family support. The conclusion of this study confirms that although Balinese women workers strive to achieve harmony within themselves, they still face challenges in fulfilling the aspect of work-life balance. Family support and effective adaptation strategies have an important role in achieving their harmonization of multi-roles. Bali dikenal dengan tradisi dan budaya yang kuat di mana perempuan memainkan peran penting dalam mempertahankan nilai-nilai tersebut. Di tengah modernisasi, perempuan generasi Z di Bali, khususnya di Kota Denpasar dan Kabupaten Badung, menghadapi tantangan dalam menyeimbangkan peran sebagai pekerja, istri, ibu, dan anggota masyarakat adat. Penelitian ini bertujuan untuk memahami bagaimana pekerja wanita Bali yang menikah pada usia muda mencapai harmonisasi dalam dirinya di tengah kompleksitas multi peran yang dijalani. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Sampel penelitian terdiri dari empat wanita Bali generasi Z yang telah menikah dan bekerja di sektor pemerintahan, swasta, atau wirausaha di Kabupaten Badung dan Kota Denpasar. Data dikumpulkan melalui wawancara mendalam, observasi partisipasi pasif, dan dokumentasi, yang kemudian dianalisis menggunakan model Miles dan Huberman dengan bantuan perangkat lunak NVivo 14. Hasil penelitian menunjukkan bahwa pekerja wanita Bali mengalami konflik peran, konflik waktu, dan konflik perilaku, yang berdampak pada work-family conflict serta work stress. Faktor utama yang memengaruhi ketidakseimbangan ini meliputi triple roles, quarter life crisis, marriage culture shock, dan job hopping. Untuk mengatasi tantangan tersebut, para informan menerapkan strategi coping seperti work-life balance strategies, manajemen peran, manajemen waktu, outsourcing, serta dukungan keluarga. Kesimpulan penelitian ini menegaskan bahwa meskipun pekerja wanita Bali berupaya mencapai harmonisasi dalam dirinya, mereka masih menghadapi tantangan dalam memenuhi aspek work-life balance. Dukungan keluarga dan strategi adaptasi yang efektif memiliki peran penting dalam mencapai harmonisasi diri mereka menjalani multi peran.